Teachers Attitude Towards Autonomous Learning in University Studies - Tandzegolskiene, Ilona; Rutkiene, Ausra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
An appropriate and considerate choice of the study methods is an important condition for successful organization of the student learning process. A teacher can contribute to the common skills’ development and student’s autonomy by thoroughly combining various methods. This specific approach not only makes the learning process more interesting and encourages student’s participation, but is also associated with student’s responsibility, self-control and motivation, skills of learning process regulation, gained experience, learning planning and creation of appropriate learning environment. The study shows that teachers emphasize the importance of tools, methods and teacher-student cooperation. In the discussion of the tools and methods which enhance student autonomy during the studies, it is suggested to change traditional lectures by experiments, case studies, learning from experience, scientific projects, i.e., when students are engaged into interesting and long term activities which are practice-oriented, develop knowledge and help to gain experience.